The Effects of Government and State Ownership on Dividends - Siti Salwani, Abdullah (2011)
This study aims to investigate the relationship between government ownership and dividend policy of Malaysian listed companies. The study used a sample of 400 companies which were randomly chosen. Two dependent variables were used as a proxy for dividend namely the dividend per share (DPS) and dividend payout ratio (DPR), while 8 government agencies (EPF, LTH, KWAP, LTAT, MKD, KNB, PNB and STATE) represented the government ownership. Since dividends are truncated, the Tobit model was utilized to examine the effect of government ownership. The findings showed that the there is no relationship between government ownership and dividend when using DPS as dependent variable. However, when DPR is used, the result showed that government ownership could affect the dividend policy. Furthermore, it is found that privately funded government agencies were more likely to affect dividend. This result indicates that these government agencies are rather influence the proportion of earnings distribution or the payable amount than the amount of dividend per unit of shares.